2008
DOI: 10.5694/j.1326-5377.2008.tb01887.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of tinea capitis in newly arrived migrants at an English‐language school, Melbourne, 2005

Abstract: Objective: To investigate a reported increase in tinea capitis in an English‐language school to determine if it was an outbreak and whether control measures were warranted. Design: Cross‐sectional study. Setting and population: Primary school children enrolled at an English‐language school in an outer suburb of Melbourne were screened for tinea capitis in November 2005 by clinical examination, collection of scalp, skin or nail specimens where clinically indicated, and scalp brushing. Main outcome measures: Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Similar to other studies, which described a transfer of M. audouinii by immigrants or travellers on vacation in countries endemic for the dermatophyte to Western countries our index patients therefore brought M. audouinii to Munich. Further transmission then occurred in kindergartens and later by older siblings of newly infected children to schools.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to other studies, which described a transfer of M. audouinii by immigrants or travellers on vacation in countries endemic for the dermatophyte to Western countries our index patients therefore brought M. audouinii to Munich. Further transmission then occurred in kindergartens and later by older siblings of newly infected children to schools.…”
Section: Discussionsupporting
confidence: 86%
“…A marked increase over the years in previously rarely isolated dermatophytes, T. soudanense , T. violaceum and Microsporum audouinii , has been noted recently 9,10 . Historically, tinea capitis was associated with Microsporum canis and T. tonsurans , but, as Figure 2 reveals; T. violaceum was the commonest dermatophyte isolated from our patients in 2008/09, with T. soudanense third, behind M. canis.…”
Section: Discussionsupporting
confidence: 49%
“…The changing epidemiology of this infection has implications for clinical recognition and therapy. Migration from Africa since the 1990s is a significant factor in the increasing number of total and previously rarely seen scalp dermatophytes 9,10 . Most of our patients with T. violaceum and all of those with T. soudanense and M. audouinii were born in Africa.…”
Section: Discussionmentioning
confidence: 86%
“…In this study we confirmed the high prevalence of dermatophytoses in children originating from developing countries , particularly Africa and the Caribbean. All of the dermatophytes were anthropophilic, representing a real public health concern.…”
supporting
confidence: 85%